Evaluation of Potential Drug-Drug Interactions in Hospitalized Pediatric Patients with Bronchitis Diagnosis: A Retrospective Study - Neda Taner; Müferiye Eskitoğlu; Betül Şirin (Journal of Pharmaceutical Care, 2023)
Background: Acute bronchitis is one of the most common infectious diseases in children and a major cause of hospital admissions. Treatment of acute bronchitis is usually symptomatic, analgesics and antipyretics are often used. The simultaneous intake of drugs brings pharmacological interactions with it. These interactions are important for the success of the treatment. The aim of our investigation is to determine the prevalence and severity of possible drug interactions; draw attention to drug interactions in children and adolescents. Methods:  This study was conducted on 99 patients, 48 ​​males and 51 females, with bronchitis hospitalized between 2019 and 2021 in Rize, Turkey. Patient records were retrospectively evaluated, and drug interactions were determined using database Medscape data by clinical pharmacists. Data was analyzed by SPSS 15.0v. statistical program p<0.05 was considered significant. The severity of the interactions was assessed as an alternative to serious use, close monitoring and minor interactions. Results: In this study, it was found that the mean age of the patients was 5.17 ± 2.31 years. A total of 69 drug-drug interactions were identified, most of which (63.6%) were identified on the ‘Close Monitor', and the interaction rate at the 'Serious Use Alternative' level was found to be 16.2%. There was no interaction in some patients in this study; but some patients experienced up to 4 interactions. Conclusion: Healthcare professionals should be more cautious about polypharmacy and more aware of the rational use of drugs. By raising awareness of drug interactions among healthcare professionals, drug interactions can be minimized.